Simulation-Based Design of a Solar PV Water Pumping System for Deep-Well Irrigation: A Case Study in Damascus - Adil Adam; Adnan Alahmad; Samer Diab (Journal of Power, Energy, and Control, 2026)
This study presents a simulation-based design of a solar photovoltaic (PV) water pumping system for deep-well irrigation in Damascus, Syria, where water scarcity and unreliable grid electricity constrain agricultural productivity. The objective is to develop a technically feasible and economically viable solar-powered alternative to conventional diesel-based pumping systems. This study contributes by integrating site-specific hydraulic requirements with PVsyst-based simulation for high-head irrigation conditions. The proposed system is designed and analyzed based on site-specific climatic and hydraulic conditions, including a daily water demand of 104 m³ and a total dynamic head of 160 m. The system configuration consists of a 4.2 kWp PV array (21 modules), a submersible pump (PS4000 C-SJ8-15), and an MPPT-based controller. Simulation results indicate that the system can reliably meet the required water demand under local solar irradiance conditions (~5.5 kWh/m²/day), achieving an overall system efficiency of 38.89%. Comparative analysis suggests that, despite higher initial capital costs, the solar-powered system offers significant long-term economic advantages due to near-zero operating costs, with an estimated payback period of 3–4 years. The findings demonstrate that solar PV water pumping is a viable and sustainable solution for high-head irrigation in semi-arid regions such as Damascus, with strong potential to reduce dependence on fossil fuels and improve agricultural resilience.